Immunocharacterisation of lymphoid organs in brown-marble grouper, Epinephelus fuscoguttatus (Forsskal, 1775) - Mazlan, Aini Nadia (2021)
Aquaculture in Malaysia has been expanded and developed to be one of the economic potentials of the country. The grouper industry in Malaysia however, has been hindered by massive issues associated with infectious diseases. As a consequence, understanding immunology in this commercially important species is vital. The current study aimed to give essential insight into the differences in immunological robustness between these lymphoid organs in the humoral or cellular functional studies. Tissue leukocytes were isolated from brown-marble grouper's lymphoid organs (spleen, head kidney, and guts) (Epinephelus fuscoguttatus). Leukocytes isolated were used to profile the phenotypic characterization of leukocytes by flow cytometric scattering profile and immunofluorescent staining of CD8α+, humoral functional studies like respiratory burst assay, lysozyme assay, and myeloperoxidase assay. Immunofluorescent staining of CD8α+ demonstrated that the gut had a significantly higher CD8α+ cell population (4.44 ± 0.53%) and upon dividing the CD8α cells based on size, the grouper spleen possessed a significantly higher percentage of large CD8α+ cell size (2.89 ± 0.43%). Meanwhile, the gut had the most abundant of small-sized CD8α+ (3.33 ± 0.45%). On the other hand, among the tested humoral and cellular functional assays, activated gut resident leukocytes recorded strong humoral immune reactions and cellular immune reactions. In humoral immune reaction, the gut has strong robustness in both respiratory burst and myeloperoxidase assay with (1.01 ± 0.05) and (120.11 ± 26.62) respectively. In addition, the gut showed a higher immune reaction in cellular immune reactions of phagocytosis assay with (3.97 ± 01.24%). As for the humoral and cellular immune reactions that will further promote pro-inflammatory responses, such as lysozyme assay and lymphoproliferation assay grouper gut showed weaker immune robustness compared to the head kidney and spleen. In lysozyme assay, head kidney and spleen were more robust with (0.36±0.03) and (0.31±0.35) respectively. Overall, the present study demonstrated that different grouper lymphoid organs have varying immune responses robustness depending on the tested immune parameter. According to the result, as a mucosal lymphoid organ, the grouper gut had more robust immune responses upon activation than the systemic lymphoid organs. This can be observed in both assays of phagocytosis and respiratory burst and myeloperoxidase assay. However, the gut showed weaker immune responses in the lymphoproliferation and lysozymes assay. This indicated that the grouper gut has weaker robustness in the immune reactions that can trigger more pro-inflammatory responses. This might be a beneficial mechanism to maintain intestinal homeostasis and to protect the resident gut commensal microbiota. The current study gives valuable insight into the differences in the immune functionality and robustness of different lymphoid organs. These findings can facilitate future research to choose the suitable lymphoid organs to be assayed for the selected functional tests, which in turn enable accurate evaluation of the target treatment in grouper.